PENDEKATAN GURU KELAS DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI KELAS VI SDS IT AL- FURQAN TAHUN PELAJARAN 2023-2024 - Eli Asih; Nuraini, Nurlisa (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Education aims to develop both spiritual and physical aspects of students gradually to achieve a well-rounded personality as individuals, social beings, and devoted servants of God. This study explores how teachers enhance student motivation at SDS IT Al-Furqan, Tebas District, Sambas Regency, through both teacher-centered and student-centered approaches. Using a qualitative descriptive methodology, which includes observation, interviews, and documentation, the research provides an in-depth understanding of teaching practices. The findings reveal that while the teacher-centered approach at the school involves modifications to create a more conducive learning environment, it still remains focused on the teacher as the primary source of knowledge. In contrast, the student-centered approach emphasizes active student engagement and the use of diverse methods such as discussions, projects, and peer teaching to boost motivation. The conclusion indicates that, although the teacher-centered approach provides a solid foundation, a more effective motivational strategy often combines elements of both approaches to create a more enjoyable and motivating learning experience.